Writing direction and language activation affect how Arabic-English bilingual speakers map time onto space - Park, Juana; Gagné, Christina L.; Spalding, Thomas L. (Frontiers in Psychology, 2024)
We investigated whether writing direction and language activation influence how bilingual speakers map time onto space. More specifically, we investigated how Arabic-English bilingual speakers conceived where (e.g., on the left or on the right) different time periods (e.g., past, present, future) were located, depending on whether they were tested in Arabic (a language that is written from right to left) or in English (a language that is written from left to right). To analyze this, participants were given a task that involved arranging cards depicting different scenes of a story in chronological order. Results show that, when tested in Arabic, participants were significantly more likely to use right-to-left arrangements (following the Arabic writing direction), compared to when tested in English.